Homens na enfermagem: vivências dos primeiros graduados na Escola de Enfermagem da Universidade Federal de Minas Gerais (década de 1970) - Carla Aparecida de Carvalho (2021)
Contextualization of the theme: Men in nursing are known especially for their work as caregivers in military services and religious orders, assisting the sick and wounded during the Crusades and, later on, in civil wars. However, in the contemporary age, the teaching model known as Nightingalean privileged women and did not allow men to enter nursing schools. However, with the shortage of professionals after World War II, men began to be admitted to regular courses. They received little encouragement from nursing schools, and it is important to unveil the experiences of this group during their undergraduate studies in nursing. Justification: There are few studies that portray the history of men in nursing and in the context of Minas Gerais nursing, in the almost 90 years of existence of the Nursing School of the Federal University of Minas Gerais (EEUFMG) no work addresses the experiences of men as students at that school. Guiding question: How did the first men inserted in the EEUFMG experience graduation in the 1970s? General objective: To analyze how the first men experienced graduation at EEUFMG in the 1970s. Specifics objectives: To understand how the professional choice of men took place in undergraduate nursing; understand what it was like to be a man in a nursing school with a female predominance. Methodological path: This is a socio-historical study, with a qualitative approach, whose methodological framework was centered on thematic Oral History, developed through the analysis of historical documents and interviews with a semi-structured script, carried out with 10 men who graduated from the EEUFMG in the 1970s. The interviews were submitted to Thematic Content Analysis, enriched with documentary research. MAXQDA® software was used for data organization, coding and support for analysis. The ethical precepts of Resolution n. 466/2012 were respected. Three categories of analysis were constructed, namely: “Nursing carrer for men: a thought through professional choice?”; "The bad side of the choice: barriers faced by men during the undergraduate nursing course", "The good side of the choice: the benefits of being a man in the undergraduate nursing course". Results and discussion: The first category identified that nursing was not the first career option for the majority of the group. However, the opportunities arising from this profession led respondents to choose it. The second category revealed the difficulties experienced by men during their academic career, pointing out the care for the opposite sex as one of the obstacles. Finally, the third category presented the benefits of choosing a career, showing that men are privileged because they are the minority in the occupation. Final considerations: this study allowed to rescue the history of nursing, cooperating to unveil the male experiences during the undergraduate nursing course at the EEUFMG in the 1970s. It was identified that the choice of the course allowed to experience both sides: good and bad. It is recommended that the study be extended to the following decades, addressing the advances that have occurred in nursing programs with the inclusion of men in the course.